2018
DOI: 10.1002/ajmg.a.38611
|View full text |Cite
|
Sign up to set email alerts
|

A parent‐of‐origin analysis of paternal genetic variants and increased risk of conotruncal heart defects

Abstract: The association between conotruncal heart defects (CTHDs) and maternal genetic and environmental exposures is well studied. However, little is known about paternal genetic or environmental exposures and risk of CTHDs. We assessed the effect of paternal genetic variants in the folate, homocysteine, and transsulfuration pathways on risk of CTHDs in offspring. We utilized National Birth Defects Prevention Study data to conduct a family-based case only study using 616 live-born infants with CTHDs, born October 199… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 76 publications
(83 reference statements)
2
9
1
Order By: Relevance
“…is known about the role of paternally-related genetic variants in outcomes of pregnancy, including their roles in CHD etiology [51]. We observed no statistically significant increased risk of OHDs for infants who inherited a paternally-derived copy of variant alleles in genes involved in folate, homocysteine, or transsulfuration pathways compared to infants who inherited a maternal copy of the variant allele.…”
Section: Plos Geneticscontrasting
confidence: 65%
See 2 more Smart Citations
“…is known about the role of paternally-related genetic variants in outcomes of pregnancy, including their roles in CHD etiology [51]. We observed no statistically significant increased risk of OHDs for infants who inherited a paternally-derived copy of variant alleles in genes involved in folate, homocysteine, or transsulfuration pathways compared to infants who inherited a maternal copy of the variant allele.…”
Section: Plos Geneticscontrasting
confidence: 65%
“…In this study, we determined the parent-of-origin effects for genetic variants in folate, homocysteine, and transsulfuration pathway genes and occurrence of OHDs in offspring. The majority of published studies have investigated the effects of maternal genetic variants and environmental factors on the occurrence of CHDs in general [ 12 , 55 57 ]; however, much less is known about the role of paternally-related genetic variants in outcomes of pregnancy, including their roles in CHD etiology [ 51 ]. We observed no statistically significant increased risk of OHDs for infants who inherited a paternally-derived copy of variant alleles in genes involved in folate, homocysteine, or transsulfuration pathways compared to infants who inherited a maternal copy of the variant allele.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The PoO effect occurs when a locus expressed in mothers or fathers has a causal influence on the phenotype of the infant, and it is often considered a genomic imprinting effect (Gjerdevik et al, ; Lawson, Cheverud, & Wolf, ). Some studies have detected gene PoO effects in birth defects, such as nonsyndromic orofacial clefts (Garg et al, ) and conotruncal heart defects (Nembhard et al, ). However, no study has reported PoO effects for PCP pathway genes related to the occurrence of NTDs.…”
Section: Discussionmentioning
confidence: 99%
“…POE have been described in congenital heart defects [86], attention deficit-hyperactivity disorder [87], testicular germ cell tumors [88], cleft lip [89], autism [90,91], language impairment [92], type II diabetes [93,94], adiposity [95], and BMI [96]. Some of these SNPs are located in proximity to imprinted genes; further evaluation is needed to determine whether all of these effects are mediated by the~100 imprinted genes in the human genome, or whether there are additional processes that affect asymmetry in the maternal and paternal genomes.…”
Section: Non-equivalence Of Maternal Vs Paternal Allelesmentioning
confidence: 99%